Bottom Slamming ; Deck Wetness; Analisis Dinamika Kapal Ikan Berlambung Katamaran terhadap Fenomena Bottom Slamming dan Deck Wetness - Chris Jeremy Verian Sitorus; Wira Setiawan; Alamsyah; Muhammad Anjas Syam; Cindy Lionita Agusty; Jusma Wahidah; Hariyono; Harlian Kustiwansa; Husein Syahab; Fernanda Wahyu Pratama; Irham Bahri (Politeknik Negeri Madura, 2025)
The lack of consideration for safety in fishing boat design, as builders primarily focused on maximizing catch. It was necessary to calculate deck wetness and bottom slamming to prevent dangerous conditions in rough weather. This study aimed to determine the RAO values of a catamaran fishing boat at wave angles of 0°, 90°, 135°, and 180°, and to calculate the probability of bottom slamming and deck wetness. The RAO calculation used an optimization method with Maxsurf software for load variations of 25% DWT, 50% DWT, and 100% DWT. The results showed that the highest heave amplitude occurred at 100% DWT, 6.45 knots, and a 0° wave angle, measuring 0.131 meters. The highest pitch amplitude was 2.02 degrees under the same conditions, while the highest roll amplitude occurred at 50% DWT, 6.45 knots, and a 90° wave angle, reaching 3.43 degrees. The probability of deck wetness was 0.24%, and bottom slamming was 0.0000000014996%, both meeting NORDFORSK 1987 standards.